2018
DOI: 10.1111/jiec.12743
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Influence of Food Waste in Food Packaging Environmental Performance Assessments

Abstract: SummaryScrutiny of food packaging environmental impacts has led to a variety of sustainability directives, but has largely focused on the direct impacts of materials. A growing awareness of the impacts of food waste warrants a recalibration of packaging environmental assessment to include the indirect effects due to influences on food waste. In this study, we model 13 food products and their typical packaging formats through a consistent life cycle assessment framework in order to demonstrate the effect of foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 47 publications
0
80
0
Order By: Relevance
“…Muangmala () found that packaging was responsible for as little as 0.3% of the GHG emissions for resource‐intensive food products, such as red meat, but about 20% of the GHG emissions for low resource‐intensive food products such as blueberries and raspberries. In an extensive literature review, Heller and colleagues () calculated the food‐to‐packaging ratio in terms of GHG emissions for a large variety of products; the reported ratios varied between 0.06 and about 700. As the ratios vary so much among different products, it is essential to understand the total environmental burden of the packaging system by considering the trade‐offs between product protection, packaging environmental footprint, packaging recycling, and FLW to make informed decisions about packaging for sustainable development.…”
Section: Understand the Total Environmental Burden Of Product/packagementioning
confidence: 99%
See 1 more Smart Citation
“…Muangmala () found that packaging was responsible for as little as 0.3% of the GHG emissions for resource‐intensive food products, such as red meat, but about 20% of the GHG emissions for low resource‐intensive food products such as blueberries and raspberries. In an extensive literature review, Heller and colleagues () calculated the food‐to‐packaging ratio in terms of GHG emissions for a large variety of products; the reported ratios varied between 0.06 and about 700. As the ratios vary so much among different products, it is essential to understand the total environmental burden of the packaging system by considering the trade‐offs between product protection, packaging environmental footprint, packaging recycling, and FLW to make informed decisions about packaging for sustainable development.…”
Section: Understand the Total Environmental Burden Of Product/packagementioning
confidence: 99%
“…), the protective role of the packaging is one of the more important functions (Heller et al. ; Hellström and Olsson ; Licciardello ; Verghese et al. ; Wikström and Williams ).…”
Section: Understand the Total Environmental Burden Of Product/packagementioning
confidence: 99%
“…For instance, modified atmosphere packaging extends shelf life, but a certain percentage of the environmental impacts were found to be cancelled out by the increased impacts from packaging functionalization (Conte, Cappelletti, Nicoletti, Russo, & Del Nobile, ; Gutierrez, Meleddu, & Piga, ; Zhang et al., ). Moreover, the pattern of trade‐offs between the benefit and the environmental impact increase from packaging functionalization of 24 food products were analyzed by Heller and colleagues (). They reported that the effectiveness of FLW reduction depended on the relative contribution of packaging to the environmental impacts.…”
Section: Introductionmentioning
confidence: 99%
“…However, the production costs are high because technology to replace traditional ink in fact is not compliant and production yields are low . The production and use of natural ink will also provide an advantage for food packaging . This will minimize migration which is unavoidable in printed products, and the human health risks arising from migration.…”
Section: Introductionmentioning
confidence: 99%
“…6 The production and use of natural ink will also provide an advantage for food packaging. 7 This will minimize migration which is unavoidable in printed products, and the human health risks arising from migration. As is known, of all the printing inks, the migration of coloring agents, photo initiators, solvents, and oils occur more due to their low molecular weights.…”
Section: Introductionmentioning
confidence: 99%